CGG Repeat Expansion, and Elevated Fmr1 Transcription and Mitochondrial Copy Number in a New Fragile X PM Mouse Embryonic Stem Cell Model - Gazy, Inbal; Miller, Carson J.; Kim, Geum-Yi; Usdin, Karen (Frontiers in Cell and Developmental Biology, 2020)
The Fragile-X related disorders (FXDs) are Repeat Expansion Diseases (REDs) that result from expansion of a CGG-repeat tract located at the 5' end of the FMR1 gene. While expansion affects transmission risk and can also affect disease risk and severity, the underlying molecular mechanism responsible is unknown. Despite the fact that expanded alleles can be seen both in humans and mouse models in vivo, existing patient-derived cells do not show significant repeat expansions even after extended periods in culture. In order to develop a good tissue culture model for studying expansions we tested whether mouse embryonic stem cells (mESCs) carrying an expanded CGG repeat tract in the endogenous Fmr1 gene are permissive for expansion. We show here that these mESCs have a very high frequency of expansion that allows changes in the repeat number to be seen within a matter of days. CRISPR-Cas9 gene editing of these cells suggests that this may be due in part to the fact that non-homologous end-joining (NHEJ), which is able to protect against expansions in some cell types, is not effective in mESCs. CRISPR-Cas9 gene editing also shows that these expansions are MSH2-dependent, consistent with those seen in vivo. While comparable human Genome Wide Association (GWA) studies are not available for the FXDs, such studies have implicated MSH2 in expansion in other REDs. The shared unusual requirement for MSH2 for this type of microsatellite instability suggests that this new cell-based system is relevant for understanding the mechanism responsible for this peculiar type of mutation in humans. The high frequency of expansions and the ease of gene editing these cells should expedite the identification of factors that affect expansion risk. Additionally, we found that these cells have abnormalities consistent with what is seen in human premutation (PM) carriers including elevated mitochondrial copy numbers and Fmr1 hyperexpression, that we show here are O2-sensitive. Thus, this new stem cell model should facilitate studies of both repeat expansion and the consequences of expansion during early embryonic development.